God and Coitus: Between Misogyny and Feminism - Calabuig Cañestro, Noemí (Anales del Seminario de Historia de la Filosofía, 2017)
The objective of this work is to point out that for a philosophical reflection on the sexes, there are two vitally important issues that are intimately related: the meaning we attribute to the intercourse and how we understand the human being relationship with the absolute (or with God). For that purpose, we will resort to the philosophies of two authors who represent antagonistic views on this matter: Otto Weinigner, an undoubtedly misogynist author, and Simone de Beauvoir, a precursor of feminism. Since their speeches coincide in many relevant aspects —for both indentify masculine values with human values, believe that women have been deceived and support the femininity disappearance— the reason why they merit opposite judgments must be found in their discrepancies. Here we support that the fundamental divergence between these theories lies in the meaning they ascribe to the intercourse. This meaning depends on how they understand the relationship between the human being and divinity. The comparison between these two authors reveals the essential nature of such issues for the philosophical discourse on the sexes.
Keywords: Beauvoir; ethics; existentialism; feminism; metaphysics; misogyny; sex; Weininger.